Sustainable development for underground mining of strategic industrial minerals: the geological and geotechnical modelling as a key factor. The case of the "Marmorino" mineral deposit (Sacile - NE Italy). Issue 1 (August 2021) - Gabriele, P; Damiano, A; Varrone, D; Piovano, V; Cravero, M; Castelli, E; Anselmi, B
Abstract: The growing industrial minerals demand, in the perspective of a sustainable development of mining activities, implies a strong orientation to underground operations in the near future. In complex geological areas, for the definition of a reliable 3D ore body model a methodological approach, aimed to improve geological and geotechnical model reliability allows a confident mineral deposit evaluation and a reliable mine design, or, in other terms, costs reduction, safety increase and mining project sustainability. The described method finds its maximum application in complex geological and structural contexts, such as the Valmadonna-Pedemonte "Marmorino" quarry.